Do State Corporate Tax Incentives Create Jobs? Quasi-experimental Evidence from the Entertainment Industry. (June 2019) - Thom, Michael
Policy makers allocate billions of dollars each year to tax incentives that increasingly favor creative industries. This study scrutinizes that approach by examining motion picture incentive programs used in over thirty states to encourage film and television production. It uses a quasi-experimental strategy to determine whether those programs have contributed to employment growth. Results mostly show no statistically significant effects. Results also indicate that domestic employment is unaffected by competing incentives offered outside the United States. These findings are robust to several alternative models and should lead policy makers to question the wisdom of targeted incentives conferred on creative industries.